Euclides Roxo e a Reforma Francisco Campos: a gênese do primeiro programa de ensino de matemática brasileiro - Werneck, Arlete Petry Terra (2003)
This study aims to analyze the inception of the first Mathematics teaching program in Brazil. This innovating program had the goal of fusing three different disciplines (Arithmetics, Algebra and Geometry) into only one discipline. The research started from reflections on the meaning of disciplinary reforms and their appropriations, and resorted to theoretical assumptions borrowed from cultural history. Its primary information source were the documents in the APER Private Files of Euclides Roxo, director and teacher of Colégio Dom Pedro II. The investigation results provided an analysis of the method used by Mr. Euclides Roxo, who, based on his interpretation of international movement for renewal of this discipline and American didactic experiences, compiled the pioneering program for teaching Mathematics in Brazil